Pathophysiology and Risk Factors for Chronic Respiratory Diseases: Review Article (Journal of Pharma Insights and Research, 2025)
Chronic respiratory diseases are a significant and growing global health burden, contributing substantially to morbidity and mortality worldwide. These heterogeneous disorders affect the airways, lung parenchyma, and pulmonary vasculature, leading to progressive physiological impairment. The pathophysiology is complex, often driven by chronic inflammation, structural remodeling, and tissue damage initiated by a variety of etiological factors. The main contributing factors include tobacco smoke, household and ambient air pollution, occupational exposures, and genetic predispositions. Moreover, emerging risk factors, such as the use of electronic cigarettes, present new challenges to respiratory health. A prominent feature of chronic lung disease is its frequent coexistence with other non-communicable diseases, a phenomenon known as multimorbidity, which complicates diagnosis, management, and patient outcomes. This pathophysiology is often mediated by shared risk factors and systemic inflammatory pathways. Addressing the global impact of these conditions necessitates a multifaceted approach. Critical imperatives include advancing diagnostic capabilities, particularly in low-resource settings, ensuring equitable access to effective treatments and pulmonary rehabilitation, and integrating palliative care for advanced stages of disease. More investment in implementation programs and targeted research is crucial for translating existing knowledge into effective public health strategies and clinical practices to alleviate the burden of chronic lung disease on a global scale